Pengembangan Media Find the Match Berbantuan Wordwall melalui Problem Based Learning Materi Jenis Hewan Meningkatkan Adversity Quotient (AQ) Siswa Kelas V SD Kabupaten Blitar - Siti Laelatul Mab’ruroh; Mohamad Fatih2; Khoirul Wafa (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study aims to develop a learning media called Find the Match, based on the Wordwall platform and implemented through the Problem-Based Learning model on the topic of animal classification to improve the Adversity Quotient of fifth-grade elementary school students. The research method used in this study is Research and Development (R&D) with the ASSURE model as the product development framework. The effectiveness of the media was tested using a quasi-experimental design, specifically a nonequivalent control group design, involving 22 students, consisting of 11 students in the experimental group and 11 students in the control group. The research data were collected through observation, interviews, questionnaires, and tests, and then analyzed using both qualitative and quantitative approaches. The validation results showed that the media was categorized from feasible to highly feasible, with expert validation percentages of 85.8% from material experts, 87.9% from media experts, 72.85% from language experts, and 72.85% from classroom teachers. The effectiveness test results indicated an increase in the average Adversity Quotient score in the experimental group from 36.27 to 44.09, with a significance value of 0.000. This improvement was higher than that of the control group. Therefore, the Find the Match media assisted by Wordwall through the implementation of the Problem-Based Learning model is proven to meet feasibility criteria and is effective in supporting the science learning process.